2017
DOI: 10.1111/irj.12167
|View full text |Cite
|
Sign up to set email alerts
|

Trade union participation in CSR deliberation: an evaluation

Abstract: Whereas there has been considerable interest in the concept of political corporate social responsibility (CSR), trade unions have been largely omitted from such scholarly discussion. This article explores the potential of trade unions as the other in political CSR and the contribution of trade unions to deliberative democracy with the firm. We discuss the importance both of the legitimacy and the efficacy of the other in political CSR. We proceed to assess trade unions as legitimate and effective deliberative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 70 publications
0
58
0
1
Order By: Relevance
“…Organisations are using CSR to strengthen its relationships with their stakeholders to ensure minimum conflicts with the stakeholders and maximum loyalty from them (Mahmoud et al 2017;Jones et al, 2017;Ali et al 2010). Existing research classifies CSR into internal and external, internal CSR which is aimed at internal operations and internal stakeholders of the company (Shen & Zhang 2019;Harvey et al, 2017;;) whereas external CSR activities involve external entities and is focused on external stakeholders (Mahmoud et al 2017;Schons & Steinmeier 2016;;Basil & Erlandson 2008;Brammer et al 2007;Peterson, 2004). Zhou et al, (2018) and Heslin & Achoa (2008) highlighted the strategic significance of CSR for corporate success while some researchers (Shen & Zhang 2019;Schons & Steinmeier 2016, Al-bdour et al 2010Eweje & Bentley 2006)) identified the importance of internal CSR measures on employee commitment (Mitonga-Monga & Hoole, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Organisations are using CSR to strengthen its relationships with their stakeholders to ensure minimum conflicts with the stakeholders and maximum loyalty from them (Mahmoud et al 2017;Jones et al, 2017;Ali et al 2010). Existing research classifies CSR into internal and external, internal CSR which is aimed at internal operations and internal stakeholders of the company (Shen & Zhang 2019;Harvey et al, 2017;;) whereas external CSR activities involve external entities and is focused on external stakeholders (Mahmoud et al 2017;Schons & Steinmeier 2016;;Basil & Erlandson 2008;Brammer et al 2007;Peterson, 2004). Zhou et al, (2018) and Heslin & Achoa (2008) highlighted the strategic significance of CSR for corporate success while some researchers (Shen & Zhang 2019;Schons & Steinmeier 2016, Al-bdour et al 2010Eweje & Bentley 2006)) identified the importance of internal CSR measures on employee commitment (Mitonga-Monga & Hoole, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this journal, Harvey et al . () have argued that CSR provides an opportunity for unions, enabling them to shape management policy and extend their influence to a new agenda. The evidence presented in this article indicates that few unions are seizing this opportunity even when civil regulation addresses a core employment issue, the Living Wage.…”
Section: Resultsmentioning
confidence: 99%
“…Coalitions might also benefit CSOs, allowing them to draw upon union resources, such as bargaining relationships with employers and political influence, to help diffuse civil regulation. A particular benefit that unions might provide to CSOs is a presence at the workplace, allowing for the monitoring and full implementation of labour standards in a manner that compensates for the lack of an ongoing workplace presence of many campaigning organisations (Heery et al ., ; Harvey et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Union democracy and collective representation have also been found to strengthen the input legitimacy of CSR (Harvey et al . ; Sobczak and Havard ).…”
Section: Towards An Er Perspective On Csr?mentioning
confidence: 98%
“…Unions in the Indonesian footwear industry have also been able to use CSR to strengthen their foothold, but also to leverage stronger implementation of labour-relevant CSR standards (Bartley and Egels-Zandén 2016). Union democracy and collective representation have also been found to strengthen the input legitimacy of CSR (Harvey et al 2017;Sobczak and Havard 2015).…”
Section: Towards An Er Perspective On Csr?mentioning
confidence: 99%